2021
DOI: 10.1177/09673911211047682
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging and characterization of HDPE pin type insulators (15 kV)

Abstract: The study of the behavior of polymeric material used for insulators in the electrical system is extremely important in order to evaluate their lifetime as well as their performance when exposed to different environmental conditions. In the present work, the behavior of high-density polyethylene (HDPE) pin type insulators (15 kV), under accelerated aging conditions, was studied. Samples were exposed to aging, for 200 h, 1000 h, and 2000 h, in accelerated weathering chambers, according to two different methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The main three methylene (>CH 2 ) group absorption peaks appeared as doublets at 2917 and 2849 cm −1 (asymmetric and symmetric stretching), 1472 and 1460 cm −1 (bending angular strain), and 730 and 718 cm −1 (rocking), respectively. 60,61 New peaks appeared due to the HDPE pipe aging in the form of a broad hydroxyl (>O-H) peak at around 3370 cm −1 , a carbonyl (>CO) peak at 1650 cm −1 , and a vinyl (>CC) peak at 909 cm −1 . 60,62 The carbonyl and vinyl indices were 0.54 and 0.64 for the new HDPE pipe, and were increased to 0.84 and 1.11, respectively, following 7 d of aging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main three methylene (>CH 2 ) group absorption peaks appeared as doublets at 2917 and 2849 cm −1 (asymmetric and symmetric stretching), 1472 and 1460 cm −1 (bending angular strain), and 730 and 718 cm −1 (rocking), respectively. 60,61 New peaks appeared due to the HDPE pipe aging in the form of a broad hydroxyl (>O-H) peak at around 3370 cm −1 , a carbonyl (>CO) peak at 1650 cm −1 , and a vinyl (>CC) peak at 909 cm −1 . 60,62 The carbonyl and vinyl indices were 0.54 and 0.64 for the new HDPE pipe, and were increased to 0.84 and 1.11, respectively, following 7 d of aging.…”
Section: Resultsmentioning
confidence: 99%
“…60,61 New peaks appeared due to the HDPE pipe aging in the form of a broad hydroxyl (>O-H) peak at around 3370 cm −1 , a carbonyl (>CO) peak at 1650 cm −1 , and a vinyl (>CC) peak at 909 cm −1 . 60,62 The carbonyl and vinyl indices were 0.54 and 0.64 for the new HDPE pipe, and were increased to 0.84 and 1.11, respectively, following 7 d of aging. By extending the degradation process up to a total Environmental Science: Water Research & Technology Paper of 14 d, unlike with the PEX-A pipes, the HDPE pipes showed enhanced degradation and the carbonyl and vinyl indices increased to 0.95 and 1.12, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…) [16]. The absorption at 2800 cm -1 -3000 cm -1 corresponding to the polyethylene bone shows the asymmetric and symmetric stretching of the (-C-H) bond of methyl group, as the main component of HDPE is aliphatic hydrocarbons, alkanes, and alkenes [17].…”
Section: Structural Propertiesmentioning
confidence: 99%
“…reduction of elongation and impact strength, change of colour or transparency, etc. [6,9,22]. Gnatowski and al.…”
Section: Introductionmentioning
confidence: 99%